PHYSIOLOGICAL EFFECT OF FEEDING ORGANIC ASCORBIC ACID ON MILK COMPOSITION AND MINERAL CONTENTS OF LACTATING COWS UNDER HEAT STRESS ENVIRONMENT - Adamu, S.; Bishir, B. B.; Ibrahim, Y.; Adamu, N.; Umar, Y. P. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was carried out to evaluate the effect of organic ascorbic acid (baobab fruit pulp meal) supplementation on milk composition and milk mineral contents of lactating Bunaji, Wadara and Friesian x Bunaji cows under heat stress environment. The experiment was conducted at the Dairy Research and Development Centre (DRDC) of Abubakar Tafawa Balewa University, Bauchi. A total of twenty-four (24) lactating cows at early, mid and late lactation were used for the research. The experimental cows were allotted to four dietary treatment diets comprising: 0.00, 5.3, 10.6 and 15.9 kg/100kg diet of BFPM respectively with six animals per treatment in a Completely Randomized Design. The data generated was subjected to analysis of variance of SPSS software. The treatments were administered once daily after milking and lasted for 186 days. For laboratory analysis of milk composition and mineral contents, 100 mls of milk per cow was collected bimonthly. Protein was higher (P<0.05) in Bunaji and Wadara breeds While milk fat was higher (P<0.05) in Bunaji and Friesian x Bunaji breeds. Also, Total Solid was higher (P<0.05) in Bunaji cows. Furthermore, Calcium and phosphorus were higher (P<0.05) in lactating cows fed 10.60 and 15.90 kg /100 kg baobab fruit pulp meal. In conclusion, BFPM at 15.9 kg/100 kg inclusion in the diet of lactating cows improve milk composition and mineral contents than other diets. It is recommended that, under tropical conditions Supplementation of BFPM should be included in the diet of lactating cows as antioxidants up to the rate of 15.9 kg/100 kg diet without any deleterious effect.